Strength of the Uninvolved Limb Following Return to Activity After ACL Injury: Implications for Symmetry as a Marker of Sufficient Strength - Matthew T Hartshorne; Jeffrey A Turner; Kenneth L Cameron; Darin A Padua (International Journal of Sports Physical Therapy)
# Background